2020
DOI: 10.1177/1729881420936091
|View full text |Cite
|
Sign up to set email alerts
|

A review on the wavelet methods for sonar image segmentation

Abstract: The sonar image segmentation is needed such as in underwater object orientation and recognition, in collision prevention and navigation of underwater robots, in underwater investigation and rescue, in seafloor object seeking, in seafloor salvage, and in marine military affairs like torpedo detection. The wavelet-based methods have the ability of multiscale and multiresolution, and they are apt at edge detection and feature extraction of images. The applications of these methods to the sonar image segmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In the field of investigation and detection of seabed pipelines, Tian et al proposed a high-resolution image texture segmentation algorithm based on wavelet transform and predicted twelve development trends in the image segmentation in the future [119]. Jiang and Zhou also introduced a back-propagation neural network to supervise the hidden details of the acoustic properties of seabed pipelines [120].…”
Section: Other Technical Applicationsmentioning
confidence: 99%
“…In the field of investigation and detection of seabed pipelines, Tian et al proposed a high-resolution image texture segmentation algorithm based on wavelet transform and predicted twelve development trends in the image segmentation in the future [119]. Jiang and Zhou also introduced a back-propagation neural network to supervise the hidden details of the acoustic properties of seabed pipelines [120].…”
Section: Other Technical Applicationsmentioning
confidence: 99%
“…Wang et al proposed an improved iris recognition method using wavelet packet and achieved remarkable results [24]. Tian et al showed the use of wavelet packets by segmenting sonar images [25]. Further, the use of wavelet packets can be found in deepfake image detection proposed by Wolter et al [26].…”
Section: Related Workmentioning
confidence: 99%
“…Algorithms that perform this process, referred to as automated object recognition (AOR), encompass state-of-the-art techniques that include decluttering, denoising, object identification, advanced image processing, and more recently deep learning artificial neural networks (ANNs) (7)(8)(9)(10). Systems utilizing AOR have been shown to reduce operator workload while retaining accuracy, allowing for expedited mission completion and the potential to improve mission quality.…”
Section: Introductionmentioning
confidence: 99%